Home » Aptitude » Algebra » Question
  1. If x + y + z = 0, then the value of
    x2 + y2 + z2
    is
    x2 - yz

    1. –1
    2. 0
    3. 1
    4. 2
Correct Option: D

x + y + z = 0
⇒ –x = y + z
⇒ (–x)2 = (y + z)2
⇒ x2 = y2 + z2 + 2yz ...(i)

∴ Expression =
x2 + y2 + z2
x2 - yz

Expression =
y2 + z2 + 2yz + y2 + z2
  { ∴ Using (i) }
y2 + z2 + 2yz - yz

Expression =
2y2 + 2z2 + 2yz
y2 + z2 + yz

Expression =
2(y2 + z2 + yz)
= 2
y2 + z2 + yz



Your comments will be displayed only after manual approval.